The Development of Interior Wall Panel from Hemp Woody Core - Konisranukul, Wanarat; Tuaycharoen, Nuanwan; Soratron, Suyada (Journal of Building Energy & Environment, 2019)
This research is focused on the study of how to develop interior wall panel from hemp woody core. Three types of adhesives; Urea-formaldehyde adhesive (UF) , Isocyanate- based adhesive ( E- Zero) and Shellac ( lac) were mixed with hemp material to create sample hemp boards using hydraulic hot press machine. The physical and mechanical properties of the panels: density, moisture content, percentage of swelling, modulus of rupture and elasticity, and internal bond strength were determined according to the specifications of Thai Industrial Standard (TIS) 876 – 2547) Then, thermal insulation properties of the boards were tested. Results indicated that hemp board with shellac adhesive meet most of the requirements as per Thailand industrial Standard specification. Some of the properties i.e. density, moisture content, and internal bond of hemp boards with all three types of adhesives were found higher than the required value of Thailand Standard specification ( 876 – 2547) . Test results on thermal and physical properties showed that the hemp boards with UF and E-Zero binding exhibited a considerably good thermal insulation.